Litígio judicial entre paciente e cirurgião plástico em Minas Gerais - Menezes, Jorge Antonio de [UNIFESP] (2017)
INTRODUCTION: The number of complaints against physicians has increased in Brazil, especially in plastic surgery. This may be attributed to deterioration in the physician-patient relationship and patient dissatisfaction with the surgical outcome. Few studies on the causes of these lawsuits are available. OBJECTIVE: To determine the main causes of complaints regarding plastic surgery and evaluate the influence of the expert report on trial results. METHODS: Assessment of claims against plastic surgeons with a court decision rendered between April 2000 and March 2015 by the Court of Justice of Minas Gerais of second instance. RESULTS: The main complaint (31%) was dissatisfaction with the general surgical outcome, followed by unsightly scar (25%), and asymmetries (11%). Of the cases where the expert conclusions favored the physician, 64% were considered unfounded in the first and second instances; 23% were upheld in both instances; and 13% had the decision changed from well-founded to unfounded in the second instance. Of the cases where the expert conclusions favored the patient, 91% were upheld in both instances, and 9% had the decision changed from unfounded to well-founded in the second instance. Overall, 46% of cases were upheld and 43% were considered unfounded in both instances. Only 11% of cases had the decision changed from the first to the second instance. CONCLUSIONS: Most of patient complaints were related to events inherent to the surgical procedure, predicted as eventual complications. The expert conclusions were instrumental for the court decision in favor of or against the plastic surgeon. In most cases, the first instance decision was upheld at the second instance.